Implementasi Kegiatan Informasi Publik Pada Dinas Pekerjaan Umum Dan Penataan Ruang Kota Palangka Raya - Wati, Indi Waras; Pratama, Niksan; Andriawan, Deden; Elvanisba, Osy; Lemu, Dory Silvan Geriding Sangka (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service activity "IMPLEMENTATION OF PUBLIC INFORMATION ACTIVITIES IN THE DEPARTMENT OF PUBLIC WORKS AND SPATIAL PLANNING OF THE CITY OF PALANGKARAYA" was carried out from July 10 2023 to September 1 2023, consisting of 4 STMIK Palangkaraya students.In this report, the Department of Public Works and Spatial Planning (Dinas PUPR) is faced with complaints management and licensing problems, as well as the difficulties faced by the public in reporting complaints regarding city facilities. The solution involves anti-drug themed videos, SIMBG service brochures, and fecal waste brochures. The expected output is a drug warning video and informative brochures. The implementation method involves designing brochures and videos based on themes and field needs. The PUPR Department's partnership plays an important role. The results of 2 months of activities produced three outputs: SIMBG brochures and fecal waste brochures as well as anti-drug videos. Community service via video helps public awareness about the impact of drugs. Suggestions include responsibilities, application of learning in practical field work, and understanding the job description at the PUPR Service. In this way, this program has succeeded in increasing the effectiveness of services, making permits easier, and facilitating public complaints about city facilities.